HUBUNGAN PENYULUHAN PEMERIKSAAN PAYUDARA SENDIRI (SADARI) TERHADAP PENGETAHUAN DETEKSI DINI KANKER PAYUDARA - Mardiah, Mardiah; Rahman, Abd; Fauziah, Henny; Hartoko, Rahadi Arie; Syamsuddin, Darussalam (Jurnal Kesehatan, 2025)
Breast cancer is the most common type of cancer affecting women, with low level of early detection awareness, particularly in Indonesia. Knowledge of early detection through Breast Self-Examination (BSE) plays an important role in reducing the incidence of breast cancer. This study aimed to analyze the relationship between health education on BSE and the improvement of early breast cancer detection knowledge among female students of the Medical Education Study Program Universitas Islam Negeri Alauddin Makassar. A quasi-experimental method with a one-group pretest-posttest design was employed involving 83 female medical students. Data were collected using a questionnaire and analyzed using the Wilcoxon test due to the non-normal distribution of the data. The results showed a significant increase in respondents’ knowledge after receiving health education on BSE. The Wilcoxon test indicated a statistically significant difference before and after the intervention (p < 0.05), suggesting a relationship between health education and improved early detection knowledge of breast cancer. Therefore, health education on BSE is proven to be effective in enhancing knowledge of early breast cancer detection.